Translation as the Doctrine of Inter-genre and Trans-genre Communication: A Semioethic Perspective - Petrilli, Susan (TTR, 2005)
AbstractThe proposal of ‘translation semioethics’ with its focus on inter-genre and trans-genre communication, that is, communication among singularities, arises in the context of global semiotics developed in the direction of semioethics. Translation semioethics contributes to underlining the need for the humanism of alterity by contrast with the humanism of identity.